PERAN ASOSIASI EKSPORTIR DAN INDUSTRI KOPI INDONESIA (AEKI) DALAM MENINGKATKAN STANDAR MUTU DAN DAYA SAING EKSPOR KOPI INDONESIA DI PASAR EROPA - Shera Nur Izzah; Umi O. Retnaningsih (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
European countries are potential market for Indonesian products such as coffee. However, the European Union has policies for imported products that are demanding in terms of environmentally friendly requirements. Indonesian coffee export has been challenged with Common Code for the Coffee (4C) for sustainability. This research describes the roles of Asosiasi Eksportir Industri Kopi Indonesia (AEKI) to improve Indonesian coffee’s quality.This qualitative research utilized secondary data with document analysis. The data came from books, journals, news from newspapers, official documents of Indonesian Statistic Bureau, and websites related to the topic. To analyze the data, researcher used level analysis of group with theory of export and international trade.The research shows that AEKI played significant roles for helping Indonesian coffee farmer to comply with European Union’s requirements, that is sustainability. Several actions have been done through funding for better seeds, fertilizer, and harvest so the quality of coffee bean can comply with the demand. National and international promotions was also done to market the product worldwide. The last but not the least, education for traditional coffee farmers to be competitive exporter players. Key Words: Export, Coffee, Indonesian Coffee Exporters and Industry Association, Common Code for the Coffee Community, Sustainability